2019
DOI: 10.14202/ijoh.2019.38-48
|View full text |Cite
|
Sign up to set email alerts
|

Vibriosis and Aeromonas infection in shrimp: Isolation, sequencing, and control

Abstract: Background and Aim: Shrimp is one of the most commonly consumed types of seafood. It is a very nutritious healthy food. Shrimp is low in calories and rich in protein and healthy fats. It also contains a treasure trove of vitamins and minerals. On the negative side, it may be affected by many bacterial diseases which affect its health. Furthermore, it may be incriminated as a vector of foodborne illnesses that range from mild gastrointestinal upset to life-threatening diseases. This study was designed to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
1
9
1
Order By: Relevance
“…Table 3 showed that among the 116 examined samples, the overall prevalence of Aeromonas was 21.55% (25 samples). These results are higher than what was recorded by Fadel & El-Lamie (2019) who recorded prevalence of infection as 16 (9.41%) of 170 tested shrimp.…”
Section: Prevalence Of Aeromonas Infectionscontrasting
confidence: 71%
See 1 more Smart Citation
“…Table 3 showed that among the 116 examined samples, the overall prevalence of Aeromonas was 21.55% (25 samples). These results are higher than what was recorded by Fadel & El-Lamie (2019) who recorded prevalence of infection as 16 (9.41%) of 170 tested shrimp.…”
Section: Prevalence Of Aeromonas Infectionscontrasting
confidence: 71%
“…On the negative side, many bacterial diseases infect them to affect their health and compromise the hygiene. They can also be charged as a vector of foodborne infections ranging from mild gastrointestinal upset to life-threatening diseases (Fadel & El-Lamie, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of this gene is a strong evidence of pathogenic potential of A. hydrophila isolates [22,23,38]. The production of these virulence properties have been known to contribute to pathogenesis and disease in humans [8,38]. The pathogenesis is that of a toxicoinfection with symptoms including fever, diarrhoea and abdominal pain [39].…”
Section: Virulence Factors Of a Hydrophila From Selected Water Sources For Household Consumption In Makurdimentioning
confidence: 99%
“…Reports show that a greater risk of infection occurs in young children, elderly people and immune compromised patients [7]. Virulence in A. hydrophila is multifactorial, with disease resulting from the production of various virulent factors including haemolytic, cytotoxic and enterotoxigenic properties [8].…”
Section: Introductionmentioning
confidence: 99%
“…Upon entering a host, bacteria need to upregulate genes required for colonization and establishing an infection, including cell surface appendages for attachment to surfaces, secretion systems for delivery of toxins, and enzymes for digestion of macromolecules for nutrient acquisition (1-5). Vibrios are Gram-negative bacteria that are found in the marine environment, and many of these bacteria are also pathogens of a variety of fish and shellfish (6)(7)(8)(9)(10). Notably, some vibrios are potent human pathogens such as Vibrio cholerae, Vibrio parahaemolyticus, and Vibrio vulnificus.…”
Section: Introductionmentioning
confidence: 99%